INCREASING STIIDENTS' MOTIVATION TO LEARN ENGLISH GRAMMAR THROUGH POETRY - Suswati Hendriani (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
The problem that interests the writer to write this paper is that many students, even those of English major, lack of motivation to learn English Grammar. As predicted, they usually have poor grammar mastery. Therefore, an altemative solution is presented here: using poetry to teach English Grammar. The purpose of the research article to show the readers how the uses of poetry can increase students' motivation in learning English Grammar. Based on the collected data through interview, questionnaire, and observation during English Grammar teaching and learning process, poetry is proved effective to increase students' motivation to learn English Grammar. The increase of the students' motivation might be caused by the combination of the different methods of when teaching grammar using poetry, namely: using rules, using examples, and using texts to teach grammar. When using poetry to teach English Grammar, English teachers can insert into the poetry English Grammar rules, examples of English Grammatical points, and make the poetry itself as the text. The combination of the three methods of teaching grammar is proved to give much better results based on the writer's observation on students learning English Grammar at her college, based on the data collected through questionnaire, and based on the students own information when they were interviewed.